ECOTOURISM SEBAGAI SALAH SATU STRATEGI PENINGKATAN EKONOMI MASYARAKAT PESISIR DI KOTA PARIAMAN - Maswar, Fuadi; Agustar, Asdi; Ifdal, Ifdal (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2019)
Ecotourism is developed in accordance with the existing potential and natural conditions based on 3 (three) main principles, namely efforts to conserve natural resources, environmental education for the community, especially tourists, and empowering the surrounding community. The three main ecotourism destinations in Pariaman City are Angso Duo Island, Turtle Breeding and Mangrove Forest. The research is aimed to describe ecotourism activities and identify its impact to economy of pariaman local poeple in Pariaman City. The study used survey methods with qualitative and quantitative approaches. Data on the implementation of ecotourism is obtained through in-depth interviews with key informants (key informants) consisting of managers, tourists and communities using qualitative descriptive analysis. In other hand, the data related to the impact of developing ecotourism on the economy of the Pariaman local poeple is obtained through surveys of respondents consisting of pariaman locel poeple who owned economic activities both directly and indirectly with ecotourism activities using quantitative descriptive analysis. The results showed that Ecotourism activities in Pariaman City had not yet been managed according to this principle as well, but the existence of destination ecotourism had shown a positive impact on the economy of the pariaman local poeple.